1987
DOI: 10.1007/bf01014677
|View full text |Cite
|
Sign up to set email alerts
|

Variations in mouse (Mus musculus) urinary volatiles during different periods of pregnancy and lactation

Abstract: Mouse urine samples from different pregnancy and lactation periods were examined by capillary gas chromatography to assess variations in the volatile signals that may affect the endocrine function of other females. Statistically significant changes in the excretion of certain urinary volatiles were observed; from 26 readily quantifiable constituents, 14 appear to be under the endocrine control. These selected components, positively identified through mass spectrometry and retention data, and the synthetic stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…[5,6]); nonetheless, there is growing recognition of reproductive signalling via olfactory channels [7]. As in several non-primate species [8][9][10], olfactory cues of pregnancy occur in humans, possibly facilitating mother-infant recognition [11]; otherwise, the potential for olfactory gestational cues in primates has been ignored. Here, we investigate pregnancy effects on olfactory cues in a promiscuous, non-human primate, the ring-tailed lemur (Lemur catta).…”
Section: Introductionmentioning
confidence: 99%
“…[5,6]); nonetheless, there is growing recognition of reproductive signalling via olfactory channels [7]. As in several non-primate species [8][9][10], olfactory cues of pregnancy occur in humans, possibly facilitating mother-infant recognition [11]; otherwise, the potential for olfactory gestational cues in primates has been ignored. Here, we investigate pregnancy effects on olfactory cues in a promiscuous, non-human primate, the ring-tailed lemur (Lemur catta).…”
Section: Introductionmentioning
confidence: 99%
“…Volatile chemicals in the urine of kinship and non-kinship in T. belangeri: The types of volatile chemical substances in urine of kinship in T. belangeri were shown in Urine is one of the metabolic production in animals, which contains some strong volatile chemical compositions (Ma and Klemm, 1997;Raymer et al, 1986;Jemiolo et al, 1987). The current study found that volatile chemical compositions in urine for kinship T. belangeri were similar, which contains Alcohols, Alkanes, Esters, Ketones, Aldehydes and Phenol, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Ketones are reasonably common in mammalian exocrine secretions, and Albone (1984b) has cited several examples of secretions containing a few short-to medium-chain ketones. Jemiolo et al (1987) have found several saturated, unsat-urated, and methyl-branched unsaturated ketones in the urine of the house mouse, Mus musculus.…”
Section: Resultsmentioning
confidence: 99%